A review of cardiac tumors - Munasur, M.; Reddy, D.; Reddi, A.; Kleinloog, R. (SA Heart Journal, 2017)
The intention of the review is to highlight the clinical presentation and established surgical technique in the management of this relatively uncommon cardiac pathology. Intracardiac masses may be encountered by a cardiologist or cardiac surgeon, and a comprehensive knowledge of the various diagnostic modalities is therefore essential. More crucial are the likely probabilities, based on an amalgamation of the clinical features, echocardiographic and radiographic findings. If surgical management is undertaken, the intra-operative finding is ultimately correlated with the histopathological diagnosis. In the review, we emphasise the necessity of a multidisciplinary approach to management of these tumors. The cumulative experience of the various members of the team collectively enables increasingly accurate diagnoses to be made preoperatively, with appropriate surgical management carried out timeously.